Intra- and interobserver variability of image-based PASI assessments in 120 patients suffering from plaque-type psoriasis - Müller-Christmann, Christine; Alt, Christina; Uhlmann, Lorenz; Klose, Christina; Enk, Alexander; Hänßle, Holger (Journal of the European Academy of Dermatology and Venereology, 2018)
Background: The Psoriasis Area and Severity Index (PASI) is the standard for psoriasis severity assessment. However, PASI measurement is complex and subjective, frequently leading to a high intra- and interobserver variability. To date, the precise extent of variability in PASI measurements and its underlying causes remain unknown. Objective To determine the inter- and intrarater variability of image-based PASI measurements by calculating Intra-Class-Correlation-Coefficients (ICCs) and to investigate the impact of the different PASI components and specific anatomic regions on the extent of variability. Methods First, the methodology of ‘image-based’ vs. commonly used ‘live’ PASI measurements was validated in a pilot study. Next, in an observational cohort study, PASI scores of 120 patients affected by plaque psoriasis were prospectively evaluated by three formally trained physicians by means of total body images (TBI). Each observer independently performed two rounds of image-based PASI calculations in all patients at two different time points. Results Overall, 720 image-based PASI scores were calculated with a mean PASI of 8.8 (range 0.7-34.8). An interrater variability with an ICC of 0.895 and mean absolute difference (MAD) of 3.3 PASI points were observed. Intrarater variability showed a mean ICC of 0.877 and a MAD of 2.2 points. When considering specific PASI components, the highest agreement was found for the assessment of the involved body surface area (BSA), while the lowest ICCs were calculated for severity scoring of ‘scaling’ and ‘induration’. As BSA scores serve as a multiplier in the calculation of PASI, minor inaccuracies were capable of inducing a large share of variability. Conclusion The overall inter- and intrarater reliability of image-based PASI measurements in this study was good. However, physicians were formally trained and experienced, which frequently is not the case in a real-life clinical setting. Therefore, new strategies for higher standardization and objectivity of PASI calculations are needed.
Gesehen am 21.04.2020